الجملة القسمية في القرآن الكريم : دراسة تحليلية - كايد, وفاء فارس نجيب (Kulliyah Ma'arif al-Wahy wa-al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah bi-Maliziya, 2006)
This study discusses the construction and meaning of Oath Sentence in the Holy Qur’an; it examines it from both the grammatical and rhetorical perspectives, beginning with the explanation of the linguistics elements in the sentence and the correlation between the two. It also considers the mysteries of Oath and its general meaning in the shade of the Qur’an so as to elaborate the conveyed meaning (in oath sentence and its complement). This is done through examination of the Oath Verses and their classification in ways that will justify our choice and analysis as well as the discovery of their Rhetorical meanings. The study adopted the analytical inductive and descriptive method because of its appropriateness for the research; whereby the researcher gathers the basic materials from reliable sources such as the old and new books of grammar, the major sources of Qur’anic exegesis and rhetoric; she later makes an academic analysis in order to establish the meaning conveyed by this kind of sentence and its mysteries in the book of Allah (S.W.T). Among the important findings of the study is that this type of Oath Sentence is the most effective ways of making emphasis and affirmative statement because it emphasizes and glorifies the object and subject of oath, it is also used to attract the attention of the listener towards the seriousness of the object of oath and provoke his keenness towards deducing its meaning. The study further notes that both halafa and aqsama have different peculiar meanings, thus not synonyms; that deletion in this kind of sentence is necessitated by the need for simplification, intended meaning and brevity, it also guides against flabbiness and provokes thinking and guides against repudiation of the addressee.